Bank efficiency and macro-economic factors: The case of developing countries - Sok, Gee Chan; Abd Karim, Mohd Zaini (Routledge, 2010)

(untitled)
This paper examines the effects of macro-economic factors on bank efficiency of commercial banks in Asia, Middle East/North Africa, and Africa. To achieve the objective, the stochastic frontier approach (SFA) was used to simultaneously estimate the parameters of the stochastic frontier and the inefficiency model. The results show that the effect of macro-economic factors on bank efficiency differs across region. Cost inefficiency of the commercial banks in the Asian region is negatively related to the real gross domestic product per capita, credit to the private sector, and market concentration but is positively related to trade openness. Banks cost inefficiency in the Middle East/North Africa is negatively related to trade openness but is positively related to market concentration suggesting that banking market in this region should be more open to competition.